PENGARUH PENGEMBANGAN EKOWISATA BAHARI PANTAI LINAUKABUPATEN KAUR PROVINSI BENGKULU - Eska Prima Monique Damarsiwi; Yun Fitriano (Management Insight: Jurnal Ilmiah Manajemen, 2019)
The development of marine tourism is more aimed at activities with broad vision on the preservation of resources and the environment or better known as marine ecotourism. This marine tourism concept discusses the use of coastal biological resources and various small islands that prioritize environmentalpreservation. Collection of 5 research variables namely attractiveness, accessibility, Public and Private Facilities, tourism image and environmental quality as variables considered to be able to increase the development of marine ecotourism on the linau coast of lanau village. The research method in this studywas a study using a cross sectional questionnaire. The sample used in this study was 399 respondents consisting of various criteria established by the author. From the results of the study found that the attractiveness, accessibility, image and environmental quality have a significant positive effect on marine ecotourism on the Linau coast, while public and private facility factors are not significant on marineecotourism activities on the linau coast. Haliini may be due to lack of development in waters, natural habitat and natural beauty are not damaged and will be removed.